2012
DOI: 10.1258/la.2011.011025
|View full text |Cite
|
Sign up to set email alerts
|

Coping with parvovirus infections in mice: health surveillance and control

Abstract: Parvoviruses of mice, minute virus of mice (MVM) and mouse parvovirus (MPV), are challenging pathogens to eradicate from laboratory animal facilities. Due to the impediment on rodent-based research, recent studies have focused on the assessment of re-derivation techniques and parvoviral potential to induce persistent infections. Summarizing recent data, this review gives an overview on studies associated with parvoviral impact on research, diagnostic methods, parvoviral persistence and re-derivation techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 70 publications
0
19
0
4
Order By: Relevance
“…Severe clinical signs are therefore not found in mature animals because of the lack of a sufficient number of susceptible cells in tissues. General aspects of rodent parvovirus infections and their potential effects on research results have been reviewed [6,8,[166][167][168][169][170].…”
Section: Parvovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe clinical signs are therefore not found in mature animals because of the lack of a sufficient number of susceptible cells in tissues. General aspects of rodent parvovirus infections and their potential effects on research results have been reviewed [6,8,[166][167][168][169][170].…”
Section: Parvovirusesmentioning
confidence: 99%
“…The prevalence of sera positive for parvoviruses ranged from 1% to nearly 10% in Western Europe and North America, with the majority of sera being positive for MPV in studies differentiating between the two parvovirus species [12,14,15,176]. These prevalence data are based on testing at commercial laboratories and do not reflect that, despite highly specific and sensitive test methods, enzootic parvovirus infections are difficult to detect due to virus-associated characteristics [169,170]. A recent survey conducted in the USA showed that during a 24-36 month period mouse parvoviruses were detected at almost all facilities that responded to a questionnaire, with MPV being more often diagnosed than MVM [13].…”
Section: Mouse Parvovirus (Mpv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Murine norovirus (MNV) and mouse parvovirus (MPV) are among the most common adventitial viral pathogens in laboratory mice. 28,42 Both are nonenveloped viruses that are no-toriously stable in the environment and resistant to inactivation from heat, desiccation, and many common disinfectants, all of which characteristics might facilitate their transmission to and within animal facilities. 9,28,51 Although MNV may cause lethal infection in severely immunodeficient mice, 31 clinical signs are generally absent in immune-competent mice.…”
mentioning
confidence: 99%
“…28,42 Both are nonenveloped viruses that are no-toriously stable in the environment and resistant to inactivation from heat, desiccation, and many common disinfectants, all of which characteristics might facilitate their transmission to and within animal facilities. 9,28,51 Although MNV may cause lethal infection in severely immunodeficient mice, 31 clinical signs are generally absent in immune-competent mice. 24 Nonetheless, MNV has been shown to infect macrophages, dendritic cells, and B cells and is therefore likely to interfere with immunologic and inflammatory studies.…”
mentioning
confidence: 99%